Study of 3D Printing Layered Fiber Fabric Filaments as an Alternative to Polypropylene Materials in Ankle Foot Orthosis for Children with Cerebral Palsy - Muhammad Fiqran Alauddin; Susy Susmartini; Lobes Herdiman (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
Children with CP in the moderate category need to use AFO to be able to walk. AFO products with PP materials used by CP children have drawbacks because the design needs of CP children are different. The application of additive manufacture by adding a layer of fiber fabric expected to replace PP materials. The basic materials for making AFO are PLA, ABS, PETG and PC filaments with carbon and texalium fabric types. Tests are carried out through tensile and impact tests to obtain tension and impact values. The treatment factors used in the process of making specimen are lamination, type of filament, and thickness. This study uses a factorial design model, to determine the significance value of each factor using ANOVA. The results show a polycarbonate filament layered with carbon fabric with a tension of 301.064 MPa, and an impact of 40.68 J/m.